BISNIS JUAL BELI ONLINE DALAM PERSPEKTIF ISLAM - Fatriansyah, Alif Ilham Akbar (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2020)
Abstract: This study aims to find out about online shop (online business shop) in the Islamic view (Islamic law). This research is a qualitative descriptive. This study included literature to examine the written sources such as scientific journals, books reference, literature, encyclopedias, scientific articles, scientific papers, and other sources that are relevant and related to the object being studied. As for the object of study this research is in the form of texts or writings that describe and explain the business / online shop (online shopping), which becomes popular in Indonesia. Results from this study are Islam does business through online is allowed following Islamic Shari’a. While there are elements of usury, injustice, monopoly, and fraud, Prophet hinted that buying and selling is lawful while consensual (Antaradhin), for sale or through an online business as having a positive impact because it is practical, fast, and easy for the buyer. If the business by via online not following the terms and conditions described above, online business is not allowed. Keywords:. online shop, Islamic Shari’a